Compact Modular Robotic Wrist With Variable Stiffness Capability - Sun, Hyunsoo; Park, Sungwoo; Hwang, Donghyun (Institute of Electrical and Electronics Engineers, 2024)
We have developed a two-degree-of-freedom robotic wrist with variable stiffness capability, designed for situations where collisions between the end-effector and the environment are inevitable. To enhance environmental adaptability and prevent physical damage, the wrist can operate in a low-stiffness mode. However, the flexibility of this mode might negatively impact stable and precise manipulation. To address this, we proposed a robotic wrist that switches between a passive low-stiffness mode for environmental adaptation and an active high-stiffness mode for precise manipulation. Initially, we developed a functional prototype that could manually switch between these modes, demonstrating the wrist's passive low-stiffness and active high-stiffness states. This prototype was designed as a lightweight, flat-type modular device, incorporating a sheet-type flexure as the motion guide and embedding all essential components, including actuators, sensors, and a control unit, into the wrist module. Based on the functional prototype, we developed an improved version to enhance durability and functionality. The resulting wrist module incorporates a three-axis force/torque sensor and an impedance control system to control the stiffness. It measures 55 mm in height, weighs 200 g, and offers a 232.4-fold active stiffness variation.